Mild Hypothermia Attenuates the Anesthetic Isoflurane-Induced Cytotoxicity - Li, Cheng; Dong, Yuanlin; Chen, Dan; Xie, Zhongcong; Zhang, Yiying (Frontiers in Cellular Neuroscience, 2017)
The commonly used inhalation anesthetic isoflurane has been reported to induce DNA damage and cytotoxicity. However, the methods to attenuate the isoflurane-induced changes remain to be determined. Mild hypothermia has organ protection effects. We therefore set out to assess whether mild hypothermia could protect the isoflurane-induced DNA damage and cytotoxicity. Moreover, we investigated the underlying mechanisms by assessing the interaction of isoflurane and mild hypothermia on ATP level. H4 human neuroglioma cells were treated with 2% isoflurane for 3 or 6 hours with and without mild hypothermia (35℃). We assessed the cell viability by using 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay and lactate dehydrogenase (LDH) assay. We employed Western blot to detect the levels of phosphorylation of the histone protein H2A variant X at Ser139 (γH2A.X), the marker of DNA damage. Finally, we used the live cell ATP detection assay to determine the effects of isoflurane and mild hypothermia on ATP levels. Here we showed that the treatment with 2% isoflurane for 6 hours decreased the levels of MTT, and increased the levels of LHD and γH2A.X in the cells. Mild hypothermia attenuated these isoflurane-induced changes. Moreover, the treatment with 2% isoflurane for 3 hours decreased the ATP levels without affecting MTT and LDH levels. Mild hypothermia also reversed the isoflurane-induced reduction in ATP levels. These findings suggest that isoflurane may induce DNA damage and cause cytotoxicity through reducing ATP levels. Mild hyperthermia would ameliorate the isoflurane-induced DNA damage and cytotoxicity by attenuating the isoflurane-induced reduction in ATP levels.